The Asset Management and Tracking System for Technical and Vocational Education and Training (TVET) Institution Based on Ubiquitous Computing - Totok Sulistyo; Karmila Achmad; Ida Bagus Irawan Purnama (ComTech: Computer, Mathematics and Engineering Applications, 2022)
Generally, Technical and Vocational Education and Training (TVET) has numerous types of assets used for conducting various skill-based learning activities. The failure to properly manage the TVET assets can lead to inefficient operation and administration, such as difficulty in tracking the history of the asset, location, and users. The research solved the problems by developing and implementing asset management and tracking system based on ubiquitous cloud computing for movable and fixed assets. The research activities were conducted in Politeknik Negeri Balikpapan, one of ten state-owned TVET institutions in Indonesia. This system was accessed using a web and mobile application. Quick Response (QR) code was used for asset identification to make a mobile device read the code with their built-in camera. Meanwhile, the geolocation was attached to provide the spatial information of assets’ whereabouts. Then, the research adopted the 5W1H question principle, so all aspects of asset management were collected and understood. The results show that the system helps TVET to keep track of their equipment and vital inventories in realtime. Moreover, the implementation of the system has a great impact administratively and ease in delivering instantaneous data and assets history for decisionmaking to internal and external asset auditors.